Fatigue in Multiple Sclerosis: A Review of the Exploratory and Therapeutic Potential of Non-Invasive Brain Stimulation - Ayache, Samar S.; Serratrice, Nicolas; Abi Lahoud, Georges N.; Chalah, Moussa A. (Frontiers in Neurology, 2022)
Fatigue is the most commonly reported symptom in patients with multiple sclerosis (MS). It is a worrisome, frequent, and debilitating manifestation that could occur at any time during the course of MS and in all its subtypes. It could engender professional, familial, and socioeconomic consequences and could severely compromise the patients' quality of life. Clinically, the symptom exhibits motor, cognitive, and psychosocial facets. It is also important to differentiate between perceived or subjective self-reported fatigue and fatigability which is an objective measure of decrement in the performance of cognitive or motor tasks. The pathophysiology of MS fatigue is complex, and its management remains a challenge, despite the existing body of literature on this matter. Hence, unraveling its neural mechanisms and developing treatment options that target the latter might constitute a promising field to explore. A PubMed/Medline/Scopus search was conducted to perform this review which aims (a) to reappraise the available electrophysiological studies that explored fatigue in patients with MS with a particular focus on corticospinal excitability measures obtained using transcranial magnetic stimulation and (b) to assess the potential utility of employing neuromodulation (i.e., non-invasive brain stimulation techniques) in this context. A special focus will be put on the role of transcranial direct current stimulation and transcranial magnetic stimulation. We have provided some suggestions that will help overcome the current limitations in upcoming research.